1998
DOI: 10.1074/jbc.273.16.9987
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator Binding to the Annexin II Tail Domain

Abstract: Tissue plasminogen activator binds to endothelial cells via the calcium-regulated phospholipid-binding protein annexin II, an interaction that is inhibited by the prothrombotic amino acid homocysteine. We sought to identify the tissue plasminogen activator binding domain of annexin II and to determine the mechanism of its modulation by homocysteine. Tissue plasminogen activator binding to immobilized annexin II was inhibited by intact fluid phase annexin II but not by its "core" fragment (residues 25-339). Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
2
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(181 citation statements)
references
References 42 publications
(46 reference statements)
5
171
2
3
Order By: Relevance
“…Although Ax-V and Ax-II share similar calcium-binding motifs, as do all members of the annexin family (35), they differ in other important aspects, most notably in the composition of the NH 2 -terminus. Ax-II has been demonstrated on the surface of many cell types, where it can serve receptor-like functions for molecules, including Tissue Plasminogen Activator (37). In addition, the NH 2 -terminus of Ax-II can bind a p11 dimer and become linked to another Ax-II molecule via its NH 2 tail, a process that can mediate aggregation of membrane vesicles (35).…”
Section: Discussionmentioning
confidence: 99%
“…Although Ax-V and Ax-II share similar calcium-binding motifs, as do all members of the annexin family (35), they differ in other important aspects, most notably in the composition of the NH 2 -terminus. Ax-II has been demonstrated on the surface of many cell types, where it can serve receptor-like functions for molecules, including Tissue Plasminogen Activator (37). In addition, the NH 2 -terminus of Ax-II can bind a p11 dimer and become linked to another Ax-II molecule via its NH 2 tail, a process that can mediate aggregation of membrane vesicles (35).…”
Section: Discussionmentioning
confidence: 99%
“…These Hcy-mediated posttranslational modifications may have important functional consequences. In vitro studies have shown that homocysteinylation of the Cys 9 residue of annexin II, the endothelial cell surface docking protein for tissue plasminogen activator, inhibits binding (26 ). Hcy also binds the fibrinbinding domain of plasma fibronectin in vitro, inhibiting its ability to bind fibrin (24 ), and binds factor Va in vitro, making it resistant to inactivation by activated protein C (27 ).…”
Section: Discussionmentioning
confidence: 99%
“…1). Although there is no clear evidence of an obligatory interaction between t-PA and a membrane-bound receptor to initiate proteolysis, t-PA can interact with the cell surface by means of the cal cium-regulated phospholipid-binding protein annexin II (Hajjar et a!., 1998). The expression of annexin II has been detected in the developing murine CNS (Hamre et a!., 1995), but its distribution in the adult brain remains to be established.…”
Section: Expression Of Serine Proteases and Their Cognate Inhibitorsmentioning
confidence: 99%